2017
DOI: 10.13005/ojc/330427
|View full text |Cite
|
Sign up to set email alerts
|

Effect of MgO-SiO2 Ratio on the Forsterite (Mg2SiO4) Precursors Characteristics Derived from Amorphous Rice Husk Silica

Abstract: This study acquires the potential of rice husk silica for production forsterite precursors using sol-gel method. The samples preparation were conducted by mixing magnesium oxide sol from Mg(NO 3 ) 2 .6.12H 2 O with silica sol extracted from rice husk, with three different composition ratios of MgO to SiO 2 are 1:1, 2:3 and 3:2 by weight and sintered at 900 o C. The samples were characterized using Fourier transform infrared (FTIR) spectroscopy, x-ray diffraction (XRD),differential thermal analysis (DTA), follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 27 publications
1
17
0
2
Order By: Relevance
“…Based on several studies, the potential of rice husks was investigated in recognition of its high purity and reactive silica [1][2], and the solubility of the silica in an alkaline solution, thus enabling the production of rice husk silica in the form of sols. In addition, rice husk silica is known as a porous and high-grade amorphous material [3][4][5][6][7], which has the potential to become a suitable raw material for the production of various silica-based materials, such as the production of a nano-silica [1,[8][9], zeolite [10][11][12], mullite [13][14], forsterite [15][16], nepheline [17] and cordierite [18].…”
Section: Introductionmentioning
confidence: 99%
“…Based on several studies, the potential of rice husks was investigated in recognition of its high purity and reactive silica [1][2], and the solubility of the silica in an alkaline solution, thus enabling the production of rice husk silica in the form of sols. In addition, rice husk silica is known as a porous and high-grade amorphous material [3][4][5][6][7], which has the potential to become a suitable raw material for the production of various silica-based materials, such as the production of a nano-silica [1,[8][9], zeolite [10][11][12], mullite [13][14], forsterite [15][16], nepheline [17] and cordierite [18].…”
Section: Introductionmentioning
confidence: 99%
“…Plenty efforts have been performed to utilize silica rice husks to produce various silica-based materials, such as nanosilica production [13] and [14]. In our previous study, several ceramic materials derived from silica rice husks reported in the literature were borosilicate [15], carbosil [16], aluminosilicate [17], mullite [18].…”
Section: Introductionmentioning
confidence: 99%
“…Preparation of asphalt composite: rice husk silica was produced using alkali extraction method following the procedure reported in a previous study [23]. In this stage, 50 g dried husk was mixed with 500 mL of 5% KOH solution in a beaker glass, boiled for 30 min, and followed to cool to room temperature and left for 24 h. The mixture was filtered to separate the filtrate which contained silica sol.…”
Section: Methodsmentioning
confidence: 99%
“…Many researchers have investigated the potential of rice husk as an excellent source of high-grade amorphous silica, which can be extracted by relatively simple methods [13][14][15]. Due to the high surface area, high degree of amorphization, and fine particle size, rice husk silica has been shown to be a good material for the preparation and synthesis of various materials such as the production of nanosilica [16,17], borosilicate [18], carbosil [19], aluminosilicates [20], mullite [21], cordierite [22], and forsterite [23]. Taking advantage of rice husk silica characteristics, the main objective of this study is an exploration of rice husk silica to provide some insight into choosing the basic materials in design and preparation of asphalt composite for roof materials as a substitute for lightweight steel roof with a variation of silica.…”
Section: Introductionmentioning
confidence: 99%